What Do You Think of My Ink? Assessing the Effects of Body Art on Employment Chances. Issue 1 (20th November 2015) - Timming, Andrew R.; Nickson, Dennis; Re, Daniel; Perrett, David
Abstract: Using mixed design analysis of variance, this paper examines the effect of body art on job applicant hireability ratings. It employs the literatures on the social psychologies of stigma and prejudice, as well as aesthetic labor, to frame the argument. The results indicate that photos of tattooed and pierced job applicants result in lower hireability ratings compared to the control faces. The negative effect of body art on employment chances is, however, reduced for job applicants seeking non‐customer‐facing roles. In customer‐facing roles, the tattoo is associated with lower hireability ratings than the piercing. The results suggest that visible body art can potentially be a real impediment to employment. © 2015 Wiley Periodicals, Inc.